Pemanfaatan Kitosan Kepiting Bakau (Scylla serrata) dan Ion Ag+ dalam Pembuatan Lapisan Antibakteri pada Casing Handphone - Esli Yunita Sari; Donna Calistalia Ruslim; Jessica Adelia Tiono; Adolf J.N. Parhusip (FaST - Jurnal Sains dan Teknologi (Journal of Science and Technology), 2026)
Phone cases are essential for protecting mobile phones from dirt and the risk of damage. However, it may also serve as reservoirs for bacterial growth, including Staphylococcus aureus, due to frequent handling and environmental exposure. To address this issue, an antibacterial coating was developed using an epoxy resin matrix incorporated with chitosan derived from Scylla serrata and silver ions (Ag⁺) obtained from AgNO₃ as active antibacterial agents. This study aimed to evaluate the antibacterial effectiveness of Scylla serrata chitosan and Ag⁺ ions and to determine the optimal chitosan-to-Ag⁺ ratio for inhibiting Staphylococcus aureus growth on coated surfaces. An in vitro antibacterial assay was performed using the agar well diffusion method on Nutrient Agar by applying 75.36 µL of chitosan–AgNO₃ solutions at ratios of 0:1, 1:0, 1:1, 2:1, and 1:2, with epoxy resin in 99.9% absolute ethanol as the negative control and 100 ppm amoxicillin as the positive control. Antibacterial activity was assessed by measuring inhibition zone diameters, and data were analyzed using tests of normality and homogeneity followed by one-way ANOVA and the Games–Howell post hoc test. The results demonstrated that both chitosan and Ag⁺ ions exhibited significant antibacterial activity, with the highest inhibition observed for the 0:1 and 1:0 ratios, while the combined chitosan–Ag⁺ formulation at a 1:1 ratio showed the most effective synergistic antibacterial performance against Staphylococcus aureus.